Analysis of The Impact of Biochar Application on Soil Fertility and Productivity. Issue 1 (September 2021) - Anika, Nova; Marpaung, David Septian Sumanto; Bindar, Yazid
Abstract: The increase agricultural production through intensification and extensification programs does not only provide solutions to food security, but it raises several challenges in sustainable production. In addition to increasing greenhouse emissions which have an impact on global warming, increased production also escalate the production of biomass waste. Although biomass waste is more environmentally friendly than oil-based waste, without proper treatment, this solid waste will have a negative impact on the environment and the sustainability of agricultural production. The conversion of biomass waste into new technology must be adapted to the characteristics of the biomass. Several studies have shown that biomass waste has the potential to be converted into products of higher value such as biochar. Biochar is a material converted from organic waste or agricultural / plantation waste that is rich in carbon, used to increase soil productivity . The long-term advantage of biochar application for the availability of plant nutrients is related to the high stability of organic carbon. The effectiveness of biochar application depends on the biochar production process, the amount of biochar that applied, the soil characteristic, the type of crop being cultivated.